The Japan of today (Public Information and Cultural Affairs Bureau, 1963)
This new edition of Japan Today has been rewritten to take account of Japan's changing fortunes in the 1963s. It describes the recent setbacks in the country's economic and financial sectors and examines the major shifts in the political sphere. Despite the current challenges to Japan's prosperity, this is a remarkable story of postwar resurgence, material progress and social stability.